2001
DOI: 10.1302/0301-620x.83b1.10914
|View full text |Cite
|
Sign up to set email alerts
|

Trochanteric rotational osteotomy for osteonecrosis of the femoral head

Abstract: The rate of success of transtrochanteric rotational osteotomy for osteonecrosis of the femoral head may be improved if patients are preselected using MRI. We have used three criteria for selection for osteotomy (i) minor collapse of the infarcted area, loss of congruity or the crescent sign, without narrowing of the joint space or acetabular involvement (ii) patients younger than 55 years and with a painful hip (iii) patients with an intact area constituting an arc of more than 120 degrees between the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The process is technically demanding and preserves the shape of the femoral head by altering its weight-bearing status (14). However, a number of studies (1518) have indicated variable rates of success for the surgery.…”
Section: Nwb Therapymentioning
confidence: 99%
“…The process is technically demanding and preserves the shape of the femoral head by altering its weight-bearing status (14). However, a number of studies (1518) have indicated variable rates of success for the surgery.…”
Section: Nwb Therapymentioning
confidence: 99%
“…The literature suggests that surgical intervention (eg, core decompression) in patients with early stage AVN, before the presence of collapse of the femoral head may improve results. 9,[16][17][18] A metaanalytical study by Moon et al concluded that fracture type and the age of the patient were significant predictors of AVN. It reported that older children were 1.14 times more likely to develop AVN for each year of increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…1). 18) The criterion for TCVO was an arc of > 150° between the central vertical line of the femoral head and the lateral margin of the necrotic portion on the mid-coronal MRI scan (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…However, in this procedure, the greater trochanter is osteotomized and the joint capsule is circumferentially incised. The reported success rates of this technique range from 17% to 100% 17,18,19)…”
mentioning
confidence: 99%